The Influence of Health Education on Knowledge and Attitudes About Diet for Obesity Prevention in Students of SMK Mahaputra Cerdas Utama, Bandung Regency - Tasya Putriliady; Roselina Tambunan; Berlyna Saragih; Tri Ardayani (CV Media Inti Teknologi, 2023)
Diet is a method or effort to control the type and quantity of food consumed for a certain goal. Obesity is characterized as an abnormal or excessive buildup of fat that is harmful to health. Health education involves changing behaviors in a dynamic way, going beyond merely imparting knowledge or concepts from one person to another. The goal of this study was to ascertain how health education affected students at SMK Mahaputra Cerdas Utama in Bandung Regency's knowledge and attitudes regarding obesity prevention diets. The one group pretest-post test is used in this research method's pre-experimental study design. With a total of 125 respondents, proportionate stratified random sampling was employed as the sampling strategy. Test analysis using Wilcoxon. The results of the study of the knowledge variable are the p-value of 0.000 or <0.05. For the attitude variable, the p-value is 0.000 or <0.05. The conclusion of this study shows that there is an influence of health education on knowledge and attitudes about obesity prevention diets for students at SMK Mahaputra Cerdas Utama, Bandung Regency. It is recommended that students continue to adopt a healthy diet and increase physical activity that involves optimal body movement to prevent obesity.